The Effect of the SSCS (Search, Solve, Create and Share) Learning Model on Students' Science Process Skills - Salma Vania Indriani; Vica Dian Aprelia Resti; Rt. Bai Rohimah (UNIB Press, 2026)
The low level of students' science process skills in learning is still a common problem, especially due to the implementation of learning models that have not fully involved students actively in the scientific process. This study aims to analyze the effect of the use of the SSCS (Search, Solve, Create and Share) learning model on students' science process skills using a quasi-experimental research method and a Nonequivalent Control Group Design research design. The subjects of the study were students in classes consisting of class VII A as the experimental class and class VII F as the control class, with 30 students each. The research instruments consisted of a science process skills test, a science process skills observation sheet, an observation sheet on the implementation of the learning model, and a student response questionnaire. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis tests using Independent Sample t-tests through IBM SPSS Statistics 26 software. The results showed that there was an increase in students' science process skills in the experimental class using the SSCS learning model with an average post-test score of 77.33 compared to the control class with an average post-test score of 61.66. The results of the hypothesis test showed a significance value of 0.000 (<0.05), thus rejecting H0 and accepting H1. This indicates a significant effect of the SSCS learning model on improving students' science process skills. Furthermore, the results of the student questionnaire showed a positive response rate of 79.57%. Based on these results, it can be concluded that the use of the SSCS (Search, Solve, Create, and Share) model is effective in improving students' science process skills.